A diketopyrrolopyrrole-based conjugated polymer for efficient photodynamic and photothermal combination therapy under single 808 nm laser irradiation. (December 2021) - Liu, Jiawei; Xu, Xingpeng; Wang, Jing; Sang, Ruoyu; Zhang, Zhen; Chen, Jiaqi; Lu, Xiaomei; Wang, Qi; Fan, Quli
Abstract: Photodynamic therapy (PDT) and photothermal therapy (PTT) are two powerful tools to tackle cancer in the biomedical field due to their super tumor ablation efficiency and minimal damage to normal tissue. However, it is still a tricky challenge to combine these two treatment modalities into a single agent for single wavelength laser triggered efficient tumor therapy. Herein, water-soluble nanoparticles consisting of diketopyrrolopyrrole-based conjugated polymer and amphipathic Pluronic F127 were intelligently devised and fabricated, which possessed outstanding optical properties, superb biocompatibility, excellent photostability. Surprisingly, the nanoparticles exhibited moderate singlet oxygen yield (2.34%) and photothermal conversion efficiency (41.5%) under an 808 nm laser illumination, which was in favor of achieving high-performance PDT/PTT combination therapy. Moreover, the evident antitumor effect of the nanoparticles was confirmed by in vitro and in vivo experiments. This work provides a promising approach to rationally design near infrared absorbing organic polymer nanoplatforms for combination cancer therapy. Graphical abstract: Multifunctional nanoparticles based on diketopyrrolopyrrole-based conjugated polymer were successfully constructed for photodynamic/photothermal combination therapy, which was triggered by a single 808 nm laser. Image 1 Highlights: The conjugated polymer DBT could be easily obtained with high yield. The DBT NPs exhibited superior NIR-I absorption and NIR-II fluorescence emission. Such NPs possessed outstanding water-solubility, photostability, and biocompatibility. Such NPs could cause toxic hyperthermia and singlet oxygen under a single 808 laser irradiation.